2015
DOI: 10.1016/j.tins.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Anxious moments for the protein tyrosine phosphatase PTP1B

Abstract: Chronic stress can lead to the development of anxiety and mood disorders. Thus, novel therapies for preventing adverse effects of stress are vitally important. Recently, the protein tyrosine phosphatase PTP1B was identified as a novel regulator of stress-induced anxiety. This opens up exciting opportunities to exploit PTP1B inhibitors as anxiolytics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…3 A ). PTP1B is a clinically relevant treatment target for cancer and diabetes with roles in insulin and EGF signaling and anxiety (4851). In GeneMANIA, 21 genes in the BioID of RHBDL4 in HEK293 cells had predicted direct connections with PTP1B.…”
Section: Resultsmentioning
confidence: 99%
“…3 A ). PTP1B is a clinically relevant treatment target for cancer and diabetes with roles in insulin and EGF signaling and anxiety (4851). In GeneMANIA, 21 genes in the BioID of RHBDL4 in HEK293 cells had predicted direct connections with PTP1B.…”
Section: Resultsmentioning
confidence: 99%
“…So far, vanadium compounds join the failures of finding specific drugs that target PTP1B, which after enormous efforts were deemed “undruggable” by the pharmaceutical industry. However, PTP1B has received additional attention because it is a validated therapeutic target in Her2-positive breast cancer and inhibitors are discussed as a therapeutic approach to Rett syndrome and anxiety disorders [94], [95].…”
Section: Significance Of Ptp1b Inhibitionmentioning
confidence: 99%
“…We have previously reported that the small molecule trodusquemine, an aminosterol first discovered in dogfish sharks and initially investigated for its therapeutic potential against bacterial infection, obesity, cancer, and anxiety disorders 23 26 , and as a stimulant of tissue regeneration 27 , acts as a potent inhibitor of αS aggregation by reducing the rates associated with the lipid-induced nucleation and fibril amplification steps in the aggregation process 20 . In a surprising contrast, we also found that trodusquemine enhances the aggregation of Aβ 42 by increasing the rate of monomer-dependent secondary nucleation and, to a lower extent, fibril elongation, while maintaining the rate of primary nucleation almost unaffected 28 .…”
Section: Introductionmentioning
confidence: 99%